[18]Annulene put into a new perspective12. Issue 25 (8th March 2016) - Lungerich, Dominik; Nizovtsev, Alexey V.; Heinemann, Frank W.; Hampel, Frank; Meyer, Karsten; Majetich, George; Schleyer, Paul v. R.; Jux, Norbert
Abstract : From a materials perspective, [18]annulene and its precursor reveal fascinating packing motifs in the solid state. Abstract : New insights into [18]annulene were gained by looking more closely at its X-ray structure, revealing a close face-to-face stacking of 3.16 Å in a herringbone-like crystal packing. Hexadehydro[18]annulene was co-crystalized in a benzene matrix, demonstrating the stabilizing role of intercalated solvent molecules in solid annulenes.